Islamic Banking Performance Assessment Model (Maqasid Sharia) - Husni Pasarela; Saparuddin Siregar; Sugianto Sugianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
From what we know about the Islamic Bank Performance Assessment Model in general. Where in the Islamic Bank Performance Assessment Model applies the Maqashid Syariah Index Model. The application of the Islamic bank performance assessment model in Indonesia uses the Maqashid Syariah index, which is a sharia banking performance measurement model that is in accordance with the objectives and characteristics of Islamic banking. MSI was developed with 3 main factors, namely: education, the creation of justice and the achievement of welfare, where the three factors are universal. The three performance measures based on maqashidsyariah, namely education, justice, and welfare require national banks to be able to design education and training programs with moral values so that they will be able to improve the abilities and skills of employees.